Genome-wide association study between single nucleotide polymorphisms and flight speed in Nellore cattle - Valente, Tiago Silva [UNESP]; Baldi, Fernando [UNESP]; Sant'Anna, Aline Cristina; Albuquerque, Lucia Galvão [UNESP]; Costa, Mateus José Rodrigues Paranhos Da [UNESP] (Public Library of Science (PLoS), 2016)
Introduction Cattle temperament is an important factor that affects the profitability of beef cattle enterprises, due to its relationship with productivity traits, animal welfare and labor safety. Temperament is a complex phenotype often assessed by measuring a series of behavioral traits, which result from the effects of multiple environmental and genetic factors, and their interactions. The aims of this study were to perform a genome-wide association study and detect genomic regions, potential candidate genes and their biological mechanisms underlying temperament, measured by flight speed (FS) test in Nellore cattle. Materials and Methods The genome-wide association study (GWAS) was performed using a single-step procedure (ssGBLUP) which combined simultaneously all 16,600 phenotypes from genotyped and non-genotyped animals, full pedigree information of 162,645 animals and 1,384 genotyped animals in one step. The animals were genotyped with High Density Bovine SNP BeadChip which contains 777,962 SNP markers. After quality control (QC) a total of 455,374 SNPs remained. Results Heritability estimated for FS was 0.21 ± 0.02. Consecutive SNPs explaining 1% or more of the total additive genetic variance were considered as windows associated with FS. Nine candidate regions located on eight different Bos taurus chromosomes (BTA) (1 at 73 Mb, 2 at 65 Mb, 5 at 22 Mb and 119 Mb, 9 at 98 Mb, 11 at 67 Mb, 15 at 16 Mb, 17 at 63 Kb, and 26 at 47 Mb) were identified. The candidate genes identified in these regions were NCKAP5 (BTA2), PARK2 (BTA9), ANTXR1 (BTA11), GUCY1A2 (BTA15), CPE (BTA17) and DOCK1 (BTA26). Among these genes PARK2, GUCY1A2, CPE and DOCK1 are related to dopaminergic system, memory formation, biosynthesis of peptide hormone and neurotransmitter and brain development, respectively. Conclusions Our findings allowed us to identify nine genomic regions (SNP windows) associated with beef cattle temperament, measured by FS test. Within these windows, six promising candidate genes and their biological functions were identified. These results may contribute to a better comprehension into the genetic control of temperament expression in Nellore cattle.Copyright: